Efforts to Improve Student Learning Outcomes Through the Make a Match Method In Learning History in Class XI SMA Negeri 3 Bangko Pusako - Rahma Arbain, Cici; Bedriati Ibrahim; Suroyo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to find out by using the make a match method in learning history in class XI IPS 2 SMA Negeri 3 Bangko Pusako with Youth Pledge material can improve student learning outcomes. This research was conducted in class XI IPS 2 which consisted of 30 students, namely 17 female students and 13 male students. This research is Classroom Action Research or PTK. This research consisted of 2 cycles namely cycle I and cycle II. Each cycle consists of 4 phases which are planning, action implementation, observation and finally reflection. Method of data collection in this study used teacher observation sheets, student observation sheets and test questions. Based on the results of research conducted by researchers, in cycle I the results were obtained: 12 students who completed or 40% and 18 students who did not complete or 60%. Then in cycle II there was an increase, namely 27 students who completed or 90% and 3 students who did not complete or 10%. So it can be concluded that student learning outcomes per cycle that match the KKM criteria have increased by 50%.